Rainfall-induced landslides in Cameron Highland area, Malaysia - Abu Mansor Maturidi, Abdul Muaz; Kasim, Norhidayu; Abu Taib, Kamarudin; Binti Wan Azahar, Wan Nur Aifa; Md. Husain, Nadiah (IOP Publishing, 2020)
Cameron Highland is classified as one of the landslide-prone areas in Malaysia due to its hilly landform. It has been discovered that the landslides in Cameron Highland were mainly triggered by the intense rainfall since the area encountered high amount of rainfall throughout the year. This study is carried out to evaluate the correlation between the rainfall intensity- duration (I-D) and the landslide occurrences in the Cameron Highland area. Twelve cases of landslides in the study area had been selected for conducting the analysis of rainfall intensity- duration (I-D) that triggers the landslides. The important variables from the analysis such as the maximum rainfall intensity (I) and the duration of rainfall series (D) have been applied to establish the empirical rainfall intensity-duration (I-D) threshold for Cameron Highland landslide areas. Based on the study, by utilising the logarithmic scale graph and applying a power-law model from the general equation of I= αD-β , the empirical I-D threshold for Cameron Highland landslide was determined as I = 29.088D-0.075 (I = rainfall intensity in mm/hr and D = duration in hour). The empirical (I-D) threshold can be a functional mechanism for the Early Warning System (EWS) once it is further developed, that enable the relevant authority to prepare mitigation measures such as evacuation, spreading information to the civilian in order to prevent major losses and casualties due to the landslide events